New derivatives of silybin and 2,3-dehydrosilybin and their cytotoxic and P-glycoprotein modulatory activity - Dzubák, Petr; Hajdúch, Marián; Gazák, Radek; Svobodová, Alena; Psotová, Jitka; Walterová, Daniela; Sedmera, Petr; Kren, Vladimír (Bioorganic & medicinal chemistry, 2006)
Large series of O-alkyl derivatives (methyl and benzyl) of silybin and 2,3-dehydrosilybin was prepared. Selective alkylation of the silybin molecule was systematically investigated. For the first time we present here, for example, preparation of 19-nor-2,3-dehydrosilybin. All prepared silybin/2,3-dehydrosilybin derivatives were tested for cytotoxicity on a panel of drugs sensitive against multidrug resistant cell lines and the ability to inhibit P-glycoprotein mediated efflux activity. We have identified effective and relatively non-cytotoxic inhibitors of P-gp derived from 2,3-dehydrosilybin. Some of them were more effective inhibitors at concentrations lower than a standard P-gp efflux inhibitor cyclosporin A. Another group of 2,3-dehydrosilybin derivatives also had better inhibitory effects on P-gp efflux but a cytotoxicity comparable with that of parent 2,3-dehydrosilybin. Structural requirements for improving inhibitory activity and reducing toxicity of 2,3-dehydrosilybin were established. Effect of E-ring substitution as well as an influence of the substituent size at the C-7-OH position of A-ring on P-gp-inhibitory activity was evaluated for the first time in this study.
Keywords: Cell Survival; Silybin; stereoizomerie; Drug Screening Assays, Antitumor; Humans; ATP Binding Cassette Transporter, Subfamily B, Member 1; Tumor Cells, Cultured; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; oxidace-redukce; alkylace; Alkylation; lidé; chemorezistence; zvířata; myši; proliferace buněk; magnetická rezonanční spektroskopie; molekulární struktura; Stereoisomerism; Mice; nádorové buňky kultivované; Molecular Structure; silibinin; P-glykoprotein; silymarin; Cell Proliferation; screeningové testy protinádorových léčiv; nádorové buněčné linie; Oxidation-Reduction; Silymarin; Animals; Cell Line, Tumor; Magnetic Resonance Spectroscopy; Drug Resistance, Neoplasm; viabilita buněk